PENGARUH KOMITE AUDIT, UKURAN PERUSAHAAN, DAN PROFITABILITAS TERHADAP VOLUNTARY DISCLOSURE - Sjahputra, Andri (Sekolah Menengah Kejuruan (SMK) Pustek, 2019)
Good Corporate Governance (GCG) is a manifestation of correct financial statements. The goal is stakeholders giving trust on the company. Therefore, it is necessary to analyze Voluntary Disclosure. This study aims to examine the influence of audit committees, firm size and profitability to voluntary disclosure. This study uses secondary data from manufacturing companies listed on Indonesian Stock Exchange 2012-2016. This research use purposive sampling method and get sample as many as 19 companies. Thereafter, the audit committee, firm size, profitability and voluntary disclosure were tested using multiple linear regression analysis using panel data contained in SPSS. Prior to the regression test, the data were first tested using the classical assumption test with a predetermined standard level of significance ie by 0.05. The results show that: (1) Audit Committee has no significant influence on Voluntary Disclosure, (2) Company size has significant effect on Voluntary Disclosure, (3) Profitability has no effect on Voluntary Disclosure, (4) Audit Committee, Company Size and Profitability simultaneously affect Voluntary Disclosure